Intervertebral Disc Degeneration: Functional Analysis of Bite Force and Masseter and Temporal Muscles Thickness - Bettiol, Nicole Barbosa; Regalo, Simone Cecilio Hallak; Cecilio, Flávia Argentato; Gonçalves, Ligia Maria Napolitano; de Vasconcelos, Paulo Batista; Lopes, Claire Genoveze Gauch; Andrade, Lilian Mendes; Regalo, Isabela Hallak; Siéssere, Selma; Palinkas, Marcelo (Prague medical report, 2022)
Intervertebral disc degeneration is a pathological condition associated with the intervertebral disc and is related to functional alterations in the human body. This study aimed to evaluate the maximum molar bite force and masseter and temporal muscles thickness in individuals with intervertebral disc degeneration. Thirty-two individuals were divided into two groups: those with degeneration of intervertebral discs (n=16) and those without degeneration (n=16). The maximum molar bite force (on the right and left sides) was measured using a dynamometer. Masseter and temporal muscle thickness during mandibular task rest and dental clenching in maximum voluntary contraction were analysed using ultrasound. Significant differences in the left molar bite force (p=0.04) were observed between the groups (Student's t-test, p<0.05). The intervertebral disc degeneration group had a lower maximum molar bite force. No significant differences in muscle thickness were observed between the masseter and temporal muscles in either group. However, based on clinical observations, the group with intervertebral disc degeneration presented less masseter muscle thickness and greater temporal muscle thickness in both mandibular tasks. Degenerative disease of the intervertebral discs promoted morphofunctional changes in the stomatognathic system, especially in maximum molar bite force and masticatory muscle thickness. This study provides insight into the interaction between spinal pathology and the stomatognathic system, which is important for healthcare professionals who treat patients with functional degeneration.
Keywords: Ultrasound; musculus masseter; Bite force; Humans; Degenerative disease; degenerace meziobratlové ploténky; elektromyografie; Bite Force; Masseter Muscle; Intervertebral disc; Masticatory muscles; Temporal Muscle; Intervertebral Disc Degeneration; Electromyography; musculus temporalis; lidé; síla skusu